2011
DOI: 10.1590/s0001-37652011000200013
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of the Indo-Pacific freshwater prawn Macrobrachium equidens Dana 1852 (Decapoda, Palaemonidae) on the coast of Brazilian Amazonia, with notes on its reproductive biology

Abstract: The freshwater prawn Macrobrachium equidens, which is native species of the Indo-Pacific Region, was recorded for the first time on the Amazon coast of Brazil. This species was found to inhabit the same environment as two native Macrobrachium species, M. amazonicum and M. acanthurus, and is morphologically very similar to the latter. The identification of the species was confirmed by the genetic analysis of sequences of the mitochondrial Cytochrome Oxidase (COI) gene. A detailed description of the morphologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…Macrobrachium jelskii is popularly known in Brazil as "camarão-sossego" (Paiva & Barreto, 1960) and it is among the 19 species of Macrobrachium Spence Bate, 1868 occurring in the Brazilian territory (De Grave & Fransen, 2011;Maciel et al, 2011;Pileggi & Mantelatto, 2012;De Grave & Ashelby, 2013;Santos et al, 2013;Vera-Silva et al, 2016). The type-locality of M. jelskii is Saint-Georges, in French Guiana, but it is widely distributed throughout South America (Pileggi et al, 2013).…”
mentioning
confidence: 99%
“…Macrobrachium jelskii is popularly known in Brazil as "camarão-sossego" (Paiva & Barreto, 1960) and it is among the 19 species of Macrobrachium Spence Bate, 1868 occurring in the Brazilian territory (De Grave & Fransen, 2011;Maciel et al, 2011;Pileggi & Mantelatto, 2012;De Grave & Ashelby, 2013;Santos et al, 2013;Vera-Silva et al, 2016). The type-locality of M. jelskii is Saint-Georges, in French Guiana, but it is widely distributed throughout South America (Pileggi et al, 2013).…”
mentioning
confidence: 99%
“…A study using molecular analysis made by Iketani et al (2011) determined that the species introduced in the coastal areas of Pará was actually M. dacqueti (Sunier, 1925), but the name M. rosenbergii must be kept (Wovor and Ng 2008;ICZN 2010). Maciel et al (2011) found Macrobrachium equidens (Dana, 1852) from the Taici Creek, a tidal channel that connects the Caeté and Taperaçu Rivers, near Brangança, northeastern Pará.…”
Section: Discussionmentioning
confidence: 99%
“…There are 22 species known in Brazil (Melo 2003, Valencia and Campos 2007, Mantelatto et al 2008, Loebmann et al 2010, Maciel et al 2011, Anger 2013, Dos Santos et al 2013). To date, there are 4 known species of this genus in Maranhão, M. acanthurus (Wiegmann, 1836), M. amazonicum (Heller, 1862), M. brasiliense (Heller, 1862), and M. jelskii (Miers, 1877) (Melo 2003).…”
Section: Introductionmentioning
confidence: 99%